2015
DOI: 10.1016/j.jaci.2014.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Increased nuclear suppressor of cytokine signaling 1 in asthmatic bronchial epithelium suppresses rhinovirus induction of innate interferons

Abstract: BackgroundRhinovirus infections are the dominant cause of asthma exacerbations, and deficient virus induction of IFN-α/β/λ in asthmatic patients is important in asthma exacerbation pathogenesis. Mechanisms causing this interferon deficiency in asthmatic patients are unknown.ObjectiveWe sought to investigate the expression of suppressor of cytokine signaling (SOCS) 1 in tissues from asthmatic patients and its possible role in impaired virus-induced interferon induction in these patients.MethodsWe assessed SOCS1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
76
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 48 publications
6
76
1
2
Order By: Relevance
“…[35] Another study has recently shown that increased nuclear SOCS1 in asthmatic bronchial epithelium suppresses rhinovirus induction of innate IFNs. [36] However, our data in severe asthmatics would suggest that reduced SOCS1 in the epithelium is associated with persistent eosinophilia, which is a major risk factor for exacerbations in this population. [37] In summary, we have investigated the expression of SOCS1, SOCS2 and SOCS3 within the airways of healthy controls, mild/moderate asthmatics, and severe asthmatics.…”
Section: Discussionmentioning
confidence: 63%
“…[35] Another study has recently shown that increased nuclear SOCS1 in asthmatic bronchial epithelium suppresses rhinovirus induction of innate IFNs. [36] However, our data in severe asthmatics would suggest that reduced SOCS1 in the epithelium is associated with persistent eosinophilia, which is a major risk factor for exacerbations in this population. [37] In summary, we have investigated the expression of SOCS1, SOCS2 and SOCS3 within the airways of healthy controls, mild/moderate asthmatics, and severe asthmatics.…”
Section: Discussionmentioning
confidence: 63%
“…This is highlighted by the altered function of the epithelium in patients with asthma compared with those without [60]. Epithelial cells actively secrete immune mediators in response to environmental stimuli [61], which are different in patients with asthma compared with controls [62].…”
Section: Bronchial Epitheliummentioning
confidence: 99%
“…Moreover, they demonstrated that SOCS1 mRNA was significantly decreased in the airways of severe asthma patients when compared to mild/moderate asthma patients but that no difference was found when compared to healthy subjects. However, a recent study investigating SOCS1 and SOCS3 proteins in endobronchial biopsies showed that SOCS1, but not SOCS3, protein staining intensity was significantly increased in the bronchial epithelium of patients with asthma, as compared to healthy volunteers [20]. These observed differences could be partially explained by the fact that the data from DORAN et al [19] were obtained from whole endobronchial biopsy mRNA and, therefore, integrated several cell types, not exclusively epithelial cells.…”
mentioning
confidence: 97%
“…The severity of the population studied is different (mild/moderate versus severe asthma), with a potential specific regulation of SOCS family proteins in severe asthma. Additionally, GIELEN et al [20] found that SOCS1, but not SOCS3, mRNA expression levels are increased in primary human bronchial epithelial cells from children with severe asthma. This last finding points to the age of patients as a confounding factor, which may be crucial to understanding the biology of the SOCS proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation